Convivència de codis al teatre de Joan Brossa - Meseguer, Lluís (Caplletra. Revista Internacional de Filologia, 2002)
This article supports the importance of the relationship between verbal and visual codes in the analysis of specific sequences in the “scenic poetry” works by Joan Brossa. Thus, it evaluates examples of particular texts that reveal the multiplicity of theatrical registers and techniques, with regard to the procedures of character- or situation- building and the breaking of the communicative conventions.